Entrepreneurship Management of Islamic Boarding School Students (Santri) Based on Alumni Empowerment at Al-Khoirot Islamic Boarding School - Husni, Muhammad; Bahiyah, Khoridatul; Sholihah; Maskuro, Vina Lailatul (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
Islamic boarding schools (pesantren) play a strategic role in producing a generation of students who are not only religious but also economically independent. This study aims to describe the Management of Student Entrepreneurship Education based on alumni empowerment at the Al-Khoirot Islamic Boarding School in Malang Regency. Using a descriptive qualitative approach and case studies, data were collected from mentors, alumni, and active students through semi-open questionnaires, limited interviews, participant observation, and documentation. The results show that alumni play a significant role in training, mentoring, and managing Islamic boarding school business units. Alumni involvement is not only based on economic aspects but also on emotional ties to the alma mater. However, the implementation of entrepreneurship programs still faces challenges such as irregular training, weak coordination between units, and low student participation. With more structured and collaborative management, Islamic boarding schools can create a sustainable entrepreneurial ecosystem integrated with the educational curriculum.